Introduction - Yasmine Marcil (Diciottesimo Secolo)
The aim of this dossier is to show the interest of the periodical press of the Enlightenment in medicine, based on contributions from several European countries (Great Britain, Germany, Sweden, Switzerland and France). In the eighteenth century, discourse on health was more present in the public sphere. In addition, physicians, who played a more prominent role in literary and academic circles, took an interest in journals. The purpose of this dossier is to look more closely at periodicals as mediators of news and medical knowledge; at doctors as journals editors; and finally, at the role of periodicals in discussions or in highlighting health debates and medical innovations.